The extraordinary trajectory of the Papillomavirus through human history - Oliveira, Geilson Gomes de; Eleutério Junior, José; Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Papillomaviruses have been infecting people since the beginning of human life on earth. The most relevant chapters of this story were written by the brilliant, diverse, and prominent scientists of their respective times. However, an important part of this story is the Papillomavirus victims and their adverse situations. There have also been disputes over intellectual primacy of the discoveries and the collaborators who were not given the recognition according to the role they played. This article will guide the reader through the remarkable facts of this conflicting and interesting relationship between humans and the Papillomavirus.